Mechanistic insight on the remdesivir binding to RNA-Dependent RNA polymerase (RdRp) of SARS-cov-2. (February 2021) - Arba, Muhammad; Wahyudi, Setyanto Tri; Brunt, Dylan J.; Paradis, Nicholas; Wu, Chun
Abstract: The RNA-dependent RNA polymerase (RdRp) is a key enzyme which regulates the viral replication of SARS-CoV-2. Remdesivir (RDV) is clinically used drug which targets RdRp, however its mechanism of action remains elusive. This study aims to find out the binding dynamics of active Remdesivir-triphosphate (RDV-TP) to RdRp by means of molecular dynamics (MD) simulation. We built a homology model of RdRp along with RNA and manganese ion using RdRp hepatitis C virus and recent SARS-CoV-2 structures. We determined that the model was stable during the 500 ns MD simulations. We then employed the model to study the binding of RDV-TP to RdRp during three independent 500 ns MD simulations. It was revealed that the interactions of protein and template-primer RNA were dominated by salt bridge interactions with phosphate groups of RNA, while interactions with base pairs of template-primer RNA were minimal. The binding of RDV-TP showed that the position of phosphate groups was at the entry of the NTP channel and it was stabilized by the interactions with K551, R553, and K621, while the adenosine group on RDV-TP was pairing with U2 of the template strand. The manganese ion was located close to D618, D760, and D761, and helps in stabilization of the phosphate groups of RDV-TP. Further we identified three hits from the natural product database that pose similar to RDV-TP while having lower binding energies than that of RDV-TP, and that SN00359915 had binding free energy about three times lower than that of RDV-TP. Graphical abstract: Image 1 Highlights: A homology model of RdRp, RNA, and manganese ion was built. Remdesivir was docked to RdRp and was stable for 500 ns MD simulations. The binding of remdesivir was stabilized by the interactions with key residues. Three hits had lower binding energies than that of remdesivir.